2011
DOI: 10.1002/eqe.1122
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interaction of bridge–train system under non‐uniform seismic ground motion

Abstract: The probability that an earthquake occurs when a train is running over a bridge in earthquake-prone regions is much higher than before, for high-speed railway lines are rapidly developed to connect major cities worldwide. This paper presents a finite element method-based framework for dynamic analysis of coupled bridge-train systems under non-uniform seismic ground motion, in which rail-wheel interactions and possible separations between wheels and rails are taken into consideration. The governing equations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Xia et al , examined spatially non‐uniform seismic ground motions and argued that not considering the seismic wave propagation effect leads to unsafe results regarding the vehicle running safety during earthquakes. Du et al , extended the study of Xia et al , , taking into account the possible separations and recontact between the wheel and the rail. The results indicated that the wheel–rail separation time duration increased as the train speed increased, under non‐uniform seismic ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al , examined spatially non‐uniform seismic ground motions and argued that not considering the seismic wave propagation effect leads to unsafe results regarding the vehicle running safety during earthquakes. Du et al , extended the study of Xia et al , , taking into account the possible separations and recontact between the wheel and the rail. The results indicated that the wheel–rail separation time duration increased as the train speed increased, under non‐uniform seismic ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…They stressed the significant effect of the vertical ground motion component on the stability of the train-rail bridge system. Further studies have been conducted by Matsumoto et al (2004), Xia et al (2006), Tanabe et al (2008Tanabe et al ( , 2011a, Yau (2010) and Du et al (2012). Recently, the two last authors of the present paper proposed a scheme for the seismic response analysis of interacting (horizontally) curved railway bridges and trains (Zeng and Dimitrakopoulos (2016).…”
Section: Introductionmentioning
confidence: 76%
“…Because in the beginning, relatively small nonlinear structure, basic present linear structure, load increment can take a few bigger, in order to save computation time, when the load increases gradually, the contribution of initial stress stiffness matrix is more and more big, the tangent stiffness matrix determinant value drops rapidly, element stiffness is falling rapidly, load-deformation curve gradually flatten out. (2) Load incremental method is used to load stability analysis can only calculate the load-displacement curve of general rising period, when the incremental algorithms of to extreme value point and load-displacement curve of the slope to the zero, the tangent stiffness matrix singularity, stiffness matrix determinant is zero, no matter how small the load increment, the structure also cannot bear more load increment, and the displacement is increasing [6].…”
Section: The Proposed Methodologymentioning
confidence: 99%